2010
DOI: 10.2754/avb201079030419
|View full text |Cite
|
Sign up to set email alerts
|

Blood Plasma Metabolic Profile of Aberdeen Angus Bulls during Postnatal Ontogenesis

Abstract: Selected indicators for the metabolic profile of blood plasma in 22 Aberdeen Angus bulls reared by the extensive method were monitored during postnatal development (from 4 to 564 days of age), including total proteins, albumin, urea, creatinine, glucose, cholesterol, triacylglycerols, bilirubin, alkaline phosphatase, alanine transaminase, aspartate transaminase, tyroxin, triiodothyronine, calcium, inorganic phosphorus, magnesium, potassium, sodium, chlorides, copper, zinc and iron. In assessing the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Therefore, increased protein in blood might have reflected efficient and increased protein utilization, and development of immunity with growing. These agree with reports from other investigations [ 8 , 13 , 18 ].…”
supporting
confidence: 94%
See 2 more Smart Citations
“…Therefore, increased protein in blood might have reflected efficient and increased protein utilization, and development of immunity with growing. These agree with reports from other investigations [ 8 , 13 , 18 ].…”
supporting
confidence: 94%
“…Therefore, skeletal growth in Japanese Black calves might be higher than Shorthorn calves, and skeletal growth might have decreased with growing. The other researchers also reported the negative relationship between blood ALP and age in calves [ 3 , 18 ].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In general, glucose as an energy source is constantly required by all body cells and must be therefore maintained at adequate plasma levels (Yousefian et al, 2010). Hyperglycaemia is an expected result of stress (Hoffmayer & Parsons, 2001) and probably the most commonly used indicator of stress responses in fish, its duration depending on the fish's nutrition and water temperature (Pickering et al, 1982). Kanyilmaz and Tekellioğlu, (2016) reported that serum GLUC levels decreased linearly, whilst TAG increased quadratically with increasing dietary zeolite addition in gilthead seabream.…”
Section: Discussionmentioning
confidence: 99%
“…Blood ALP-mainly released from the liver and bones-is related to liver dysfunction and bone development in beef cattle 21,22 . In growing animals, blood ALP is mainly released from bone tissue; the main tissue that releases the ALP into the blood stream transforms into liver tissue and the overall release decreases with growth 23,24 . In Japanese Black calves, blood ALP concentrations are signi cantly lower in the late growing stage than in the early growing stage, likely due to the slower rate of bone growth with increasing age 23 .…”
Section: Discussionmentioning
confidence: 99%